Kejahatan dan Kejatuhan Manusia Menurut John Calvin: Sebuah Tanggapan Terhadap Ajaran Dualisme Manichaean - Yohanes Setiawan (Dunamis: Jurnal Teologi dan Pendidikan Kristiani)
Abstract. The concept of evil and the fall of man remains a fascinating topic as it illustrates moral complexity, freedom of choice, and its impact on civilization and man's relationship with transcendent values. This article aims to analysis the concept of Manichaean dualism and measure it against the concept of the fall of man, according to John Calvin. This research uses a literature study method. The analysis results show that Manichaean dualism is eclectic and syncretic in different contexts by combining elements from various religious traditions. In contrast, Calvin's thought is very focused on reinterpreting the Christian tradition and emphasizing the authority of the Bible. For Calvin, the concept of dualism is very erroneous and unbiblical; the fall of man and evil should be understood through the doctrine of Adam and Eve's original sin, which resulted in the fall of man into sin because of their disobedience to God.